"Non-competing social groups"? The long debate on social mobility in Italy (c. 1890-1960) - Giacomo Gabbuti (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
In the light of the recent literature on the intellectual history of inequality, this paper offers the first survey and a tentative classification of the Italian literature addressing issues related to social mobility, from late-19th century to the 'Economic Miracle' of the 1950s. During these decades, the foremost Italian economists and statisticians (among others, Pareto, Gini, Einaudi and Pantaleoni) worked on issues, from the role of inheritance to the intergenerational transmission of status, which are very related to the modern understanding of social mobility. While reflecting the evolution and debates in Italian society, these authors participated to a broader international debate, that should lead us to reconsider the lack of interest for inequality by economists in this period.
Keywords: B00; D31; D63; H24; J62; 330; Social mobility; equality of opportunity; inheritance; Italian economic thought